2016
DOI: 10.1097/icl.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Dry Eye Workshop Dry Eye Severity Grading System With Tear Meniscus Measurement by Optical Coherence Tomography and Tear Osmolarity

Abstract: Both tear osmolarity and tear meniscus OCT measurements comply with the DEWS grading system, and they can be used in the diagnosis and follow-up of dry eye patients in addition to conventional tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(34 reference statements)
1
5
0
2
Order By: Relevance
“…Garsia-Resua et al found that there is a good correlation between osmolarity and subjective grading of TMH as well as measuring of TMH using open-source software (NIH ImageJ) [19]. Both tear osmolarity and tear meniscus OCT measurements comply with the DEWS grading system as previously reported by Tukenmez-Dikmen et al [20] Mean values of TMH and LIPCOF between different grades of DE didn't show statistically significant difference, so according to our result they are not convenient for grading DE. In our study mean value of TMH in group without DE was 0.17 mm.…”
Section: Discussionsupporting
confidence: 59%
“…Garsia-Resua et al found that there is a good correlation between osmolarity and subjective grading of TMH as well as measuring of TMH using open-source software (NIH ImageJ) [19]. Both tear osmolarity and tear meniscus OCT measurements comply with the DEWS grading system as previously reported by Tukenmez-Dikmen et al [20] Mean values of TMH and LIPCOF between different grades of DE didn't show statistically significant difference, so according to our result they are not convenient for grading DE. In our study mean value of TMH in group without DE was 0.17 mm.…”
Section: Discussionsupporting
confidence: 59%
“…Patients with dry eye have decreased SMT values, and therefore, measuring the meniscus length and correlating it with osmolarity in these patients can yield parameters of great importance . In healthy CM, there was no significant correlation between SMT and osmolarity, in contrast to the results for humans, which might have been influenced by the significantly higher values of the LE.…”
Section: Discussionmentioning
confidence: 89%
“…Points on the grading scale that did not occur in any group are not shown. Palakuru et al 2007Palakuru et al , 2008Ibrahim et al 2010;Koh et al 2010;Chen et al 2011;Park et al 2012;Qiu et al 2012;Altan-Yaycioglu et al 2013;Fukuda et al 2013;Bartuzel et al 2014;Canan et al 2014;Sizmaz et al 2014;Akiyama et al 2015;Tukenmez-Dikmen et al 2015). For measuring precorneal tear film, the resolution of commercially available OCT systems is not sufficient for quantitative measurement.…”
Section: Discussionmentioning
confidence: 99%